A new cucurbit[10]uril-based AIE fluorescent supramolecular polymer for cellular imaging. (10th March 2022) - Luo, Yang; Gan, Shiquan; Zhang, Wei; Jia, Menghao; Chen, Lixia; Redshaw, Carl; Tao, Zhu; Xiao, Xin
Abstract : The synthesis of the AIE fluorescent supramolecular polymer TPE-B@Q[10] is reported. This system exhibits excellent blue emission properties, good biocompatibility and was successfully employed for cytoplasmic imaging of cells. Abstract : To further advance the development of cucurbit[10]uril-based supramolecular biomaterials, an AIE fluorescent supramolecular polymer (TPE-B@Q[10]) was constructed from the newly synthesized AIE molecule TPE-B and Q[10] via host–guest interactions in a host/guest ratio of 2 : 1. TPE-B@Q[10] not only has excellent blue fluorescence emission properties, but also possesses good biocompatibility and low toxicity. Therefore, TPE-B@Q[10] was successfully used for cytoplasmic imaging of cells. Flow cytometry further illustrated that Q[10] is capable of generating an alternative way to increase the fluorescence of TPE-B and its characteristic pattern for cellular imaging. This work provides a theoretical basis for promoting the application of cucurbit[ n ]uril-based supramolecular polymers in cell biology, and promotes the further development of cucurbit[ n ]uril chemistry.